2019
DOI: 10.1016/j.celrep.2019.04.101
|View full text |Cite
|
Sign up to set email alerts
|

The lncRNA SLNCR Recruits the Androgen Receptor to EGR1-Bound Genes in Melanoma and Inhibits Expression of Tumor Suppressor p21

Abstract: Highlights d SLNCR-AR complexes drive melanoma growth and invasion d SLNCR-AR complexes are recruited to EGR1-bound loci d SLCNR-AR-EGR1 complexes regulate transcription of proliferative genes d EGR1 normally activates p21; SLNCR-AR-EGR1 complexes repress p21

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 95 publications
(130 reference statements)
2
46
0
Order By: Relevance
“…Wee1 phosphorylates Cdc2 and suppresses its activity, and p21 is an inhibitor of the cyclin B1/Cdc2 kinase complex. 37) Our data demonstrated increased upregulation of p21 and Wee1 and downregulation of Cdc2 and cyclin B1 at the mRNA and protein levels during G2/M phase arrest in EC-109, Kyse-150 and Kyse-520 cells (Figs. 2, 4) and increased phosphorylation of Cdc2 (Fig.…”
Section: Discussionsupporting
confidence: 55%
“…Wee1 phosphorylates Cdc2 and suppresses its activity, and p21 is an inhibitor of the cyclin B1/Cdc2 kinase complex. 37) Our data demonstrated increased upregulation of p21 and Wee1 and downregulation of Cdc2 and cyclin B1 at the mRNA and protein levels during G2/M phase arrest in EC-109, Kyse-150 and Kyse-520 cells (Figs. 2, 4) and increased phosphorylation of Cdc2 (Fig.…”
Section: Discussionsupporting
confidence: 55%
“…Long non-coding RNAs (lncRNAs) are newlydiscovered transcripts larger than 200 nucleotides [6][7][8]. Recent research has reported that lncRNAs participate in numerous biological activities, such as apoptosis, cell differentiation and metastasis, thus contributing to cancer progression [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The 2 0 -FANA-modified oligonucleotides are incompatible with RNase H-mediated cleavage, thereby preventing downregulation of SLNCR1 or other potential off-target RNAs ( Figure S7C; Schmidt et al, 2019). Consistent with a steric-blocking mechanism, these oligonucleotides decrease melanoma proliferation, another cancer phenotype attributed to the interaction of AR and SLNCR1, without decreasing SLNCR1 expression (Schmidt et al, 2019). Both SLNCR1-(antisense) and AR-binding (mimic) oligonucleotides sterically block the AR/SLNCR1 interaction in vitro (Figure 7B).…”
Section: Inhibiting Ar Binding Negates Slncr1-mediated Melanoma Invasionmentioning
confidence: 99%
“…In many cases, RNA-driven AR function promotes oncogenesis (Yang et al, 2013;Zhang et al, 2015). For example, our work has revealed that SLNCR1 increases AR occupancy at the promoter of the gene encoding the matrix metalloproteinase MMP9 to increase melanoma invasion, and regulates AR occupancy at the promoter of many growth-regulatory genes to increase cell proliferation (Schmidt et al, 2016(Schmidt et al, , 2019. Although AR has been implicated in multiple cancers, including prostate, bladder, kidney, lung, liver, pancreatic, thyroid, and breast cancers, the fundamental mechanisms of AR activation in many of these cancers is not well-established (Chang et al, 2014;Kanda et al, 2014;Stanley et al, 2012).…”
Section: Introductionmentioning
confidence: 95%